Enzymatic acylation of cyanidin-3-glucoside with fatty acid methyl esters improves stability and antioxidant activity. (1st May 2021) - Zhang, Pingling; Liu, Shuang; Zhao, Zhengang; You, Lijun; Harrison, Mark D.; Zhang, Zhanying
Graphical abstract: Highlights: Cyanidin-3-glucoside (C3G) was acylated with fatty acid methyl esters. The acylation of C3G with fatty acids occurred on the 6″-OH of the glucose part. Three esters were purified and characterized. C3G- n- octanoate had the highest thermostability and photostability. C3G-laurate had the highest cellular antioxidant activity. Abstract: Cyanidin-3-glucoside is a major anthocyanin in legumes, black rice, and purple potato, and has anti-inflammatory and antioxidant properties. In the present study, the effect of acylation on cyanidin-3-glucoside lipophilicity, stability, and antioxidant capacity was investigated. Cyanidin-3-glucoside was enzymatically acylated through transesterification with fatty acid esters to produce three monoacylated cyanidin-3-glucoside esters, cyanidin-3-(6″- n- octanoyl)-glucoside, cyanidin-3-(6″-lauroyl)-glucoside, and cyanidin-3-(6″-myristoyl)-glucoside. Cyanidin-3-(6″- n- octanoyl)-glucoside had the highest thermostability and photostability of the three cyanidin-3-glucoside esters. While the in vitro antioxidant activity of cyanidin-3-(6″- n- octanoyl)-glucoside was 7.5%–14.3% lower than that of cyanidin-3-glucoside ( p < 0.05), its cellular antioxidant activity increased by 33.3% ( p < 0.05). Further, while cyanidin-3-(6″-lauroyl)-glucoside had lower stability and in vitro antioxidant activity than that of cyanidin-3-(6″- n- octanoyl)-glucoside, its cellular antioxidant capacity was 125.9% and 69.4% higher than cyanidin-3-glucoside and cyanidin-3-(6″- n- octanoyl)-glucoside, respectively ( p < 0.05). This study demonstrated that transesterification can be used to improve the stability and in vivo antioxidant activity of cyanidin-3-glucoside.